Contribution Of Covid-19 Containment Measures On Epidemiology Of Diarrhea Disease Among Patients Attending Jaramogi Oginga Odinga Teaching And Referral Hospital, Kisumu County, Kenya. 2018-2021 - Omondi, Fredrick Onduru (JOOUST, 2024)
Diarrhea is the second leading cause of child morbidity and mortality, particularly in developing countries. It is the third leading cause of death in the world and continues to impose a significant burden, accounting for 2.8 billion diarrhea episodes among older children, adolescents, and adults. Severe Acute Respiratory Syndrome coronavirus type 2 (SARS-CoV-2) - Covid-19 outbreak was declared a pandemic on 11th March 2020 which prompted the implementation of ant-covid preventions and control measures in attempt to curb its transmission from person to person. The interventions were not only impactful in managing Covid-19 transmission rates, but also helped reducing the rates of infectious diarrhea diseases with associated risk factors as personal hygiene, sanitation, contact handshake, lockdown and travel restrictions. This study aimed to assess the contribution of covid-19 containment measures on epidemiology of diarrhea in the adolescent and adult patients attending Jaramogi Oginga Odinga Teaching and Referral Hospital, Kisumu County, Kenya, 2018-2021. Given the already manipulated treatments of enforced Covid-19 containment measures as intervention. The specific objectives were; to examine the trend/seasonality of diarrhea during the two time periods, to determine the current baseline estimate/ prevalence of diarrhea between the adolescence and adult age group, and to determine the influence of covid-19 containment measures on the trends of diarrhea episodes. The research provides evidence-based information of hygiene policies to diarrhea prevalence to inform decision making and priority setting. A cross-sectional retrospective survey was carried out on the entire the outpatient new client (OPD) records at 80% power, 95% CI, alpha of 0.05 and N of 345,499 to detect a smaller effect size. Descriptive statistics was used to summarize and organize the data. The relationship between the dependent variables, independent and intervening variable was explained through trend analysis, & Generalized Linear Mixed Effect Model (GLMEM Poisson log link) with both random intercept and fixed slope. The prevalence of diarrhea during covid-19 pandemic period was 0 .6% significantly lower compared to the pre covid-19 pandemic 2.7%. On average, the month of January had the highest prevalence of diarrhea (2.1%) followed by April (1.9%) & May (2%) with June registering the lowest prevalence during 2018 to 2021. During covid-19 pandemic October turned to have the highest prevalence of diarrhea. January, February and October had a significant increased rate of diarrhea 1.46, 1.26 & 1.31 respectively compared to month of April. There was a statistically significant reduction in the adjusted incidence risk of diarrhea during covid-19 by 79% (IRR = 0.21, 95% CI [0.20, 0.23], p < .001). The study finding raises the possibility that the deployed interventions against Covid-19 could have had significant effect on reducing the incidence and prevalence of diarrhea cases. Understanding the burden, trends, and prevalence of diarrheal disease, as well as its seasonal variation, is critical for developing effective control programs for the overall reduction of diarrhea disease among people of all ages.
Keywords: Covid-19